2021
DOI: 10.1055/s-0041-1731312
|View full text |Cite
|
Sign up to set email alerts
|

Ferrum phosphoricum D12 Treatment Affects J774A.1 Cell Proliferation, Transcription Levels of Iron Metabolism, Antioxidant Defense, and Inflammation-related Genes

Abstract: Background Ferrum phosphoricum (FP) is prescribed as a homeopathic remedy to treat the early stages of fever and inflammation in cases of colds or flu, muscle fatigue and anemia. We aimed to analyze the molecular mechanisms of action of FP D12 on cell proliferation and mRNA expression of iron metabolism, antioxidant defense and inflammation-related genes in mouse J774A.1 macrophages. Methods Cell proliferation was examined using the MTT test. RT-qPCR analyses were performed to estimate gene expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…And Prof Oskan Tasinov (Bulgaria) described how Ferrum phosphoricum D12 (commonly used in acute infectious inflammatory states) alters the gene expression patterns of activated macrophages in vitro. Prof Tasinov's work was a follow-on project from a study presented in HRI London 2019 11 and forms a growing body of evidence that formally assesses the bioactivity of homeopathic tissue salts, which are a particular type of homeopathic medicine available over-the-counter that have so far been under-represented in the research literature.…”
Section: Valuable Insights From a Multi-disciplinary Approachmentioning
confidence: 99%
“…And Prof Oskan Tasinov (Bulgaria) described how Ferrum phosphoricum D12 (commonly used in acute infectious inflammatory states) alters the gene expression patterns of activated macrophages in vitro. Prof Tasinov's work was a follow-on project from a study presented in HRI London 2019 11 and forms a growing body of evidence that formally assesses the bioactivity of homeopathic tissue salts, which are a particular type of homeopathic medicine available over-the-counter that have so far been under-represented in the research literature.…”
Section: Valuable Insights From a Multi-disciplinary Approachmentioning
confidence: 99%
“…9 FP is also known as "cell salt" due to its oxygen-carrying capacity and related anti-inflammatory action and is used as a firstaid remedy. 10 According to the literature, it has been reported that FP has a potential effect on anemia by improving hemoglobin levels and providing strength to blood vessels. 11 Tasinov et al reported in 2022 that FP at high dilution has iron retention, antioxidant and immunomodulatory activities in mouse macrophages, possibly by modulating transcription levels of related genes.…”
Section: Introductionmentioning
confidence: 99%
“…10 According to the literature, it has been reported that FP has a potential effect on anemia by improving hemoglobin levels and providing strength to blood vessels. 11 Tasinov et al reported in 2022 that FP at high dilution has iron retention, antioxidant and immunomodulatory activities in mouse macrophages, possibly by modulating transcription levels of related genes. 11 FP has also been found to inhibit the production of free oxygen radicals in human neutrophils.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ongoing pandemic also features in another of our papers: a study at a service sector company in Brazil, which observed a lower incidence of COVID-19 in employees who received a homeopathic medicine for disease prevention compared with those who did not receive the medication. 6 This issue of the journal is completed by two articles with an emphasis on in vitro research, 7 8 together with a clinical case report of individualized homeopathic treatment for co-morbid warts and vitiligo, 9 and a commentary article on the well-known ‘EPI3’ study in France, identifying that program of work as methodologically refined and fit for purpose. 10…”
mentioning
confidence: 99%